2014
DOI: 10.1007/s10900-014-9931-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Mailed HPV Self-testing Among Women at Higher Risk for Cervical Cancer

Abstract: Objective Whether human papillomavirus (HPV) self-testing can expand access to cervical cancer screening will depend on making the test accessible and acceptable to higher-risk women. To evaluate a novel delivery mode, we mailed HPV self-test kits to low-income, under-screened women and assessed their perceptions of self-testing and cervical cancer prevention. Materials and Methods We conducted a telephone survey of 199 women in North Carolina. Eligibility criteria included not having had a Pap test in 4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…The findings from the current study are similar to prior studies conducted among women living in other countries (Racey, Withrow, and Gesink 2013; Verdoodt et al 2015), and in recent research studies completed in the U.S. (Crosby et al 2015; Galbraith et al 2014; Montealegre et al 2015; Nelson et al 2015; Scarinci et al 2013). Most studies conducted in the U.S. have found that women were receptive to having an HPV self-test mailed to their home and to completing the test; these studies reported many of the same concerns, especially about correctly completing the test (Galbraith et al 2014; Nelson et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from the current study are similar to prior studies conducted among women living in other countries (Racey, Withrow, and Gesink 2013; Verdoodt et al 2015), and in recent research studies completed in the U.S. (Crosby et al 2015; Galbraith et al 2014; Montealegre et al 2015; Nelson et al 2015; Scarinci et al 2013). Most studies conducted in the U.S. have found that women were receptive to having an HPV self-test mailed to their home and to completing the test; these studies reported many of the same concerns, especially about correctly completing the test (Galbraith et al 2014; Nelson et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Most studies conducted in the U.S. have found that women were receptive to having an HPV self-test mailed to their home and to completing the test; these studies reported many of the same concerns, especially about correctly completing the test (Galbraith et al 2014; Nelson et al 2015). These findings were similar among immigrant women (Barbee et al 2010; Sewali et al 2015), among lesbian and bisexual women (Reiter and McRee 2015), and underserved women (Crosby et al 2015; Galbraith et al 2014; Montealegre et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that in most countries with cervical cancer screening programs, the majority of cervical cancers occur in women who have not been regularly screened [ 34 ]. Low income and low levels of education have frequently been associated with non-participation in cervical cancer screening [ 35 37 ], although the evidence is not entirely consistent [ 38 ]. Among women aged 20 to 64 in 2014 in Sweden, median annual gross income is approximately 280 000 Swedish kronor (~ $32 700 USD), with over 90% of these women earning less than 450 000 (~ $52 500 USD) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…German women aged 20–30 years, who participated in a study to self-sample by cervicovaginal lavage rated the user-friendliness of the self-sampling method as easy ( 79 ). In a telephone survey of 199 low-income women in North Carolina who had not had a Pap test in 4 years, HPV self-tests delivered by mail were perceived to be trustworthy ( 80 ). However, in a recent study among 1,769 women presenting to two University of Washington clinics for routine cervical cancer screening, about 40% of participants were concerned that self-sampling might be inferior to clinician-collected samples, although both patients as well as physicians were supportive of the concept of self-sampling for HPV testing ( 81 ).…”
Section: Women Prefer Self-sampling Over Sampling By a Healthcare Promentioning
confidence: 99%